Record of Morchella tridentina in an Abies religiosa forest in Mexico and in vitro culture of its mycelium with obtaining sclerotia - Ortega-Vargas, Claudia Ivette; Santos-Hernández, Antonio Fidel; Carrasco-Hernández, Violeta; Rodríguez-Trejo, Dante Arturo; Máxima Borja de la Rosa, Ma. Amparo; García Díaz, Silvia Edith (Instituto de Ecología, A.C., 2023)
Background and Aims: The genus Morchella groups ascomycete fungi, with several edible species of great nutritional and biotechnological importance. In China and the United States of America, species of Morchella have been artificially cultivated succesfully until producing fruiting bodies. The objectives of this work were: identify species of Morchella collected in an Abies religiosa forest, cultivate their mycelium in vitro and propagate them in wheat grains. The present study contributes to the knowledge of the initial phase necessary for the possible artificial cultivation of this group of fungi. Methods: Mushrooms were collected in an Abies religiosa forest located in Santo Tomas Apipilhuasco, Tepetlaoxtoc, Mexico State, Mexico. Fungi were identified (taxonomically and molecularly) and isolation was realized from pieces from sporome tissue in potato dextrose agar (PDA) medium, followed by propagation in wheat grains. Key results: The species collected were identified as Morchella tridentina and cultivation in vitro of mycelium in PDA was achieved as well as its propagation in wheat grains, where the formation of sclerotia was observed after 21 days of inoculation. The characteristics of the in vitro-cultured mycelium varied among strains, although they were isolated from specimens corresponding to the same species. The specimens were deposited in the CHAP Herbarium, Universidad Autónoma de Chapingo. Conclusions: Because of the presence of strains that are capable to form sclerotia, it could be used for ascocarp production. However, it is convenient to continue with this investigation with the objective of determining the optimal conditions (environmental, substrates, fruiting induction) for this aim and to achieve its artificial cultivation.